2013
DOI: 10.1080/15389588.2013.802776
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mobile Phone Use Among Motorcyclists in Three Mexican Cities

Abstract: To our knowledge this is the first study that reports the prevalence of mobile phone use while driving among motorcyclists. The observed prevalence is higher than the prevalence stated in a previous report from China on electric bicycle riders. This risk factor should be monitored in the future given the growing popularity of motorcycles and the availability of mobile devices. Current legislation should be enforced to avoid potential injuries and deaths attributable to this risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 7 publications
3
13
1
4
Order By: Relevance
“…An important factor considered in the selection of observation sites was the inclusion of both intersection and mid-block locations. Another factor was the number of lanes since previous studies have reported that mobile phone use and helmet use among motorcyclists might be different depending on road types (Hung et al, 2006;Pérez-Núñez et al, 2013). Roads with different numbers of lanes, e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important factor considered in the selection of observation sites was the inclusion of both intersection and mid-block locations. Another factor was the number of lanes since previous studies have reported that mobile phone use and helmet use among motorcyclists might be different depending on road types (Hung et al, 2006;Pérez-Núñez et al, 2013). Roads with different numbers of lanes, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study in Guadalajara-Zapopan, León, and Cuernavaca in Mexico showed that 0.64% of motorcyclists were using a mobile phone while riding (Pérez-Núñez et al, 2013). In another study in Suzhou, China, 0.4% of electric bike riders were observed to use a mobile phone (Du et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Estudios recientes estiman que, durante 2011-2012, un 10,78% y un 0,64% de un total de 7.940 automovilistas 30 y 4.244 motociclistas 31 , respectivamente, que fueron observados aleatoriamente en tres ciudades del país, utilizaban el teléfono móvil al conducir.…”
Section: • Uso De Celularunclassified
“…As such, in most countries legislation has been introduced so that only hands free use of mobile phones is allowed, if mobile phone use is allowed at all (e.g., Ibrahim, Anderson, Burris, & Wagenaar, 2011, Waddell, & Wiener, 2014. In addition to the effects on car drivers, prevalence of operating a mobile phone while riding a motorcycle have also been recently researched; Pérez-Núñez, et al (2014) observed that 0.64% operated a phone while riding a motorcycle. Again in most countries, including Mexico, operation of mobile phones while riding is illegal (Pérez-Núñez, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effects on car drivers, prevalence of operating a mobile phone while riding a motorcycle have also been recently researched; Pérez-Núñez, et al (2014) observed that 0.64% operated a phone while riding a motorcycle. Again in most countries, including Mexico, operation of mobile phones while riding is illegal (Pérez-Núñez, et al, 2014). When it comes to riding a bicycle the situation is different, and differs between countries.…”
Section: Introductionmentioning
confidence: 99%